PNEUMOCOCCAL INFECTION IN RUSSIA: EPIDEMIOLOGICAL SITUATION - I.S. Koroleva; S.M. Kharit; A.A. Ruleva; A.L. Perova; S.V. Sidorenko (Union of pediatricians of Russia, 2010)
The article features an analysis of available literature on the incidence, etiological characteristics, clinical forms of pneumococcal infections in the Russian Federation with a break-down by age group highlighting risk factors. It provides clinical and epidemiological justification for applying pneumococcal conjugated heptavalent vaccine in children as a tool to manage the disease incidence of pneumococcal infections. Key words: pneumococcal infections, meningitis, pneumonia, children, pneumococcal conjugated vaccine. (Pediatric Pharmacology. - 2010; 7(4):12-18)